THE EFFECT OF PRAGMATIC TEXTS ON STUDENTS’ READING COMPREHENSION AT THE SECOND GRADE STUDENTS OF SMA ISLAM USWATUN HASANAH CEMPAKA PUTIH IN ACADEMIC YEAR 2018/2019 - Masyudi Masyudi (JUPE : Jurnal Pendidikan Mandala, 2018)
This research aimed to find out the effect of pragmatic texts on students’ Reading Comprehension at the second grade students of SMA Islam Uswatun Hasanah Cempaka Putih in academic year 2018/2019. The method of this research was pre-experimental quantitative research. The total population of this research consisted of one class with 28 students. The technique of analyzing data was descriptive and inferential data analysis. The result showed that the students’ mean score of pre-test was 37 meanwhile the students’ mean score of post-test was 57 and the t-test score was (4.875) and t-table (2.052) from (df) 27. The result of the questionnaire showed that 80% were very agree to be taught by using pragmatic texts. Based on the result of the study, it can be concluded that the use of pragmatic texts had a positive effect on students’reading comprehension at the second grade students of SMA Islam Uswatun Hasanah Cempaka Putih in academic year 2018/2019.